15-deoxy-Δ(12,14)-PGJ(2): endogenous PPARγ ligand or minor eicosanoid degradation product? - Powell, William S. (American Society for Clinical Investigation, 2003)
15-Deoxy-Δ(12,14)-prostaglandin J(2) (15d-PGJ(2)) affects gene transcription by activating PPARγ and by covalent addition to transcription factors and signaling molecules, However, it is not known whether the high concentrations of 15d-PGJ(2) required for these responses are consistent with physiological levels. A new study suggests that in vivo 15d-PGJ(2) levels are actually several orders of magnitude below the levels required to induce many of the biological effects attributed to this molecule.